Secondhand smoke exposure and support for smoke-free policies in cities and rural areas of China from 2009 to 2015: a population-based cohort study (the ITC China Survey) - Geoffrey T Fong; Gang Meng; Lorraine Craig; Anne C K Quah; Guoze Feng; Yuan Jiang; Genevieve Sansone; Mi Yan; Steve S Xu; Changbao Wu (BMJ Open)
Objectives To examine trends in smoking prevalence in key venues (workplaces, restaurants, bars) and in public support for comprehensive smoke-free laws, with comparisons between cities and rural areas in China.Design Data are from Waves 3–5 (2009–2015) of the International Tobacco Control (ITC) China Survey, a cohort survey of smokers and non-smokers. Logistic regression analyses employing generalised estimating equations assessed changes in smoking prevalence and support for smoke-free laws over time; specific tests assessed whether partial smoking bans implemented in three cities between Waves 3 and 4 had greater impact.Setting Face-to-face surveys were conducted in seven cities (Beijing, Changsha, Guangzhou, Kunming, Shanghai, Shenyang and Yinchuan) and five rural areas (Changzhi, Huzhou, Tongren, Yichun and Xining).Participants In each survey location at each wave, a representative sample of approximately 800 smokers and 200 non-smokers (aged 18+) were selected using a multistage cluster sampling design.Main outcome measures Prevalence of smoking (whether respondents noticed smoking inside restaurants, bars and workplaces); smoking rules inside these venues; and support for complete smoking bans in these venues.Results Although smoking prevalence decreased and support increased over time, neither trend was greater in cities that implemented partial smoke-free laws. Smoking was higher in rural than urban workplaces (62% vs 44%, p<0.01), but was equally high in all restaurants and bars. There were generally no differences in secondhand smoke (SHS) exposure between smokers and non-smokers except in rural workplaces (74% vs 58%, p<0.05). Support for comprehensive bans was equally high across locations.Conclusions Partial laws have had no effect on reducing SHS in China. There is an urgent need for comprehensive smoke-free laws to protect the public from exposure to deadly tobacco smoke in both urban and rural areas. The high support among Chinese smokers for such a law demonstrates that public support is not a barrier for action.